Analytic properties of the electromagnetic field of binary compact stars and electromagnetic precursors to gravitational waves - Wada, Tomoki; Shibata, Masaru; Ioka, Kunihito (Progress of theoretical and experimental physics, 2020)
Abstract We analytically study the properties of the electromagnetic field in the vacuum around close binary compact stars containing at least one neutron star. We show that the orbital motion of the neutron star induces high multipole modes of the electromagnetic field just before the merger. These modes are superimposed to form a spiral arm configuration, and its edge is found to be a likely site for magnetic reconnection. These modes also enhance the total Poynting flux from neutron star binaries by a factor of 2–4. We also indicate that the electric field induced by the orbital motion leads to a magnetosphere around binaries and estimate its plasma density, which has a different parameter dependence than the Goldreich–Julian density. With these properties, we discuss possible electromagnetic counterparts to gravitational wave events, and identify radio precursors, such as fast radio bursts, as the most promising observational targets.